Raised from Obscurity: A Narratival and Theological Study of the Characterization of Women in Luke-Acts - Forbes, Greg; Harrower, Scott D. (s.l., 2016)
Anticipating Broader Narratival and Theological Themes in Luke-ActsChapter 4. Galilean Ministry (Luke 3:1-9:50); Jesus as the Central Narrative Character; Calling of the Disciples (Luke 5:1-11, 27-32; 6:12-16); Raising of the Widow's Son (Luke 7:11-17); Jesus anointed by a Sinful Woman (Luke 7:36-50); Women who Support Jesus (Luke 8:1-3); Jesus' True Family (Luke 8:19-21); Raising of Jairus' Daughter and the Healing of the Women with a Hemorrhage (Luke 8:40-56); Summary of Narratival Propositions; Theological Propositions; Anticipating Further Narratival and Theological Themes in Luke-Acts.
Chapter 5. Travel Narrative (Luke 9:51-19:28)Sophistication and Paradigms as Narratival Techniques; The Mission of the Seventy (Luke 10:1-24); Mary and Martha (Luke 10:38-42); The Queen of the South (Luke 11:31); Healing of a Crippled Woman on the Sabbath (Luke 13:10-17); The Parable of the Lost Coin (Luke 15:7-10); The Parable of the Judge and the Widow (Luke 18:1-8); Summary of Narratival Propositions; Theological Propositions; Chapter 6. Jerusalem Narrative (Luke 19:29-24:53); The Widow's Offering (Luke 21:1-4); Peter's Denial and the Astute Servant Girl (Luke 22:54-62).
Front cover; Half title; Title page; Copyright; Contents; Foreword by Lynn H. Cohick; Acknowledgments; Chapter 1. Introduction and Methodology; Literature Review; The Aim of this Book; A Methodology for Exploring a Narrative's Theological Claims about Its Characters; Structure and Content of the Book; Chapter 2. Women in Judaism and the Greco-Roman World; Introduction; Preliminary Comments; Women in Ancient Jewish Society; Women in Second Temple Judaism; Women in the Greco-Roman World; Conclusion; Chapter 3. The Infancy Narratives (Luke 1:5-2:52); Elizabeth; Mary; Anna.
On the Way to the Cross (Luke 23:26-31)The Death of Jesus (Luke 23:44-49); The Resurrection of Jesus (Luke 24:1-12); Summary of Narratival Propositions; Theological Propositions; Chapter 7. The Purpose and Structure of Acts; Luke's Portrayal of Women in Acts; The Purposes of Acts: Theological and Apologetic; The Structure of Acts; Chapter 8. The Birth of the Church (Acts 1-2); Acts 1; Acts 2; Summary of Narratival Propositions; Theological Propositions; Chapter 9. The Church in Jerusalem (Acts 3-12); Ananias and Sapphira (5:1-11); The Seven who Serve (Acts 6:1-7).
Tabitha-also Known as Dorcas (Acts 9:36-42)Mary Mother of John, and Rhoda (Acts 12:12-17); Summary of Narratival Propositions; Theological Propositions; Chapter 10. The Church in the Greco-Roman World (Acts 13-28); The Conversion of Lydia (Acts 16:11-40); Priscilla (Acts 18:1-28); The Daughters of Philip (Acts 21:1-16); Summary of Narratival Propositions; Theological Propositions; Chapter 11. Summary and Conclusions; Summary of Narratival Propositions in Luke and Acts; Summary of Theological Propositions in Luke and Acts; A Lukan Theology of Women; A Final Word; Bibliography; Back cover.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Criticism, interpretation, etc; Bible; Women in the Bible; RELIGION ; Biblical Studies ; Jesus, the Gospels & Acts; RELIGION ; Biblical Studies ; New Testament; Women in the Bible; Criticism, interpretation, etc